Pricing of illicit drugs on darknet markets: a conceptual exploration. Issue 2 (13th July 2020) - Zaunseder, Andreas; Bancroft, Angus
Abstract : Purpose: Trading illicit drugs on cryptomarkets differs in many ways from material retail markets. This paper aims to contribute to existing studies on pricing by studying the relationship between price changes in relation to changes in nominal value of the cryptocurrency. To this, the authors qualitatively study product descriptions and images to expand the knowledge on price formation. Design/methodology/approach: The authors analysed 15 samples based on visual and textual scrapes from two major drug markets – for Dream Market between January 2014 and July 2015 and for Tochka between January 2015 and July 2015. This longitudinal study relates changes in process to variations in the Bitcoin exchange rate and selling strategies. The analysis of the marketing of drugs online also addressed the development of the vendor profile and product offers. Findings: Product prices change in relation to variations in the Bitcoin exchange rate. This points to the application of mechanisms for automatic price adaptations on the market level. Real prices of the drug offers constantly increase. The authors assert that there is a bidirectional relationship. Vendors structure price and discounts to encourage feedback. And feedback in combination with signals of commitment and authenticity inform pricing. Product descriptions are an important feature in the successful marketization of goods, whereas product images are predominantly used as an aspect of recognisability and feature of the vendor's identity. Research limitations/implications: Findings suggest that there is great potential for further qualitative research into the relationship between the online and offline identity of drug vendors, as well as price setting when entering the market and subsequent changes for offered products. Practical implications: Findings also suggest that further investigation into the constitution and management of vendor's identity on the cryptomarkets would allow a better understanding of vendors and their interactions on cryptomarkets. Social implications: A better understanding of drug trading on cryptomarkets helps to more effectively address potentials for harm in the online drug trade. Also targetting crime would benefit from a better understanding of vendor idenities and pricing. Originality/value: The findings represent a valuable contribution to existing knowledge on drug trading on cryptomarkets, particularly in view of pricing and vending strategies.